2001
DOI: 10.1080/02701367.2001.10608955
|View full text |Cite
|
Sign up to set email alerts
|

Through the Years: A Longitudinal Study of Physical Education Teachers from a Research-Based Preparation Program

Abstract: This study investigated factors that enhanced and constrained the career development of six teachers, who had graduated from the same university teacher education program, in their induction years (Woods & Earls, 1995) and again later in their career cycles. Three participants were physical education teachers (PETs), and three were former physical education teachers (FPETs). Fessler's (1985) Teacher Career Stage Model provided the theoretical framework. Data sources were: interviews with teachers and their tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 26 publications
0
35
0
2
Order By: Relevance
“…It must be kept in mind that teachers develop differently, their careers are built differently, and the teacher career cycle is not a linear process. Hence, different stages of a teacher's career may vary between teachers, and it is possible that all career stages do not exist for all individuals (Woods & Lynn, 2001). There is also criticism of the career stage theories, because they are based on systems, on the managerial perspective of a "teacher-as-employee" rather than "teacher-asperson" perspective.…”
Section: Stages Of Teacher Careermentioning
confidence: 99%
See 1 more Smart Citation
“…It must be kept in mind that teachers develop differently, their careers are built differently, and the teacher career cycle is not a linear process. Hence, different stages of a teacher's career may vary between teachers, and it is possible that all career stages do not exist for all individuals (Woods & Lynn, 2001). There is also criticism of the career stage theories, because they are based on systems, on the managerial perspective of a "teacher-as-employee" rather than "teacher-asperson" perspective.…”
Section: Stages Of Teacher Careermentioning
confidence: 99%
“…Nowadays, however, teachers' careers are more varied and teaching careers are formed in different stages. In addition, teachers develop differently and have different skills, attitudes, knowledge and behaviours during their work-life cycle (Woods & Lynn, 2001). Over their career, teachers face different incidents and challenges that may influence motivation and job satisfaction (Day & Gu, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This stage may be the most influential factor in effective teaching performance for the rest of a teacher's occupational life, even though the teacher career cycle model maintains that many factors influence each stage of an educator's career. This argument was supported by some researchers, who indicated that teachers at the beginning year of employment have a firmly entrenched belief system that is difficult to change (Fessler & Christensen, 1992;Lynn, 2002;Woods & Lynn, 2001). Such belief system is constituted, for instance, by a teacher's negative experiences, memories, or feelings for another person or situation, which drive the teacher to exhibit unfavorable reactions to circumstances that are similar to those that fostered negativity (Fessler & Christensen, 1992).…”
Section: Introductionmentioning
confidence: 68%
“…En revanche, Soucie et Brodeur (1979) font remarquer que ce sont les nombreux problèmes de communication et de relations humaines qui affectent négativement la satisfaction au travail. Enfin, Woods et Lynn (2001) soulignent qu'en dernière analyse, ce sont surtout des facteurs personnels et organisationnels qui influencent davantage la décision de rester dans la profession ou de la quitter.…”
Section: Expérience De Travail Des Répondantsunclassified